Les usages de la fin du monde : l’apocalypse et la post-apocalypse en tant que modes narratifs - Connor Pitetti (ReS Futurae)
Through a broad survey of fictional, religious, philosophical, and political end-time narratives, this essay identifies two strategies for telling stories about the end of the world. Apocalyptic narratives use the idea of the end to give structure to the experience of history. By narrating the end as a moment of rupture that creates an absolute division between old and new worlds, they frame history as a series of clearly defined and therefore comprehensible transitions between distinct moments or epochs. Postapocalyptic narratives complicate this neatly organized account by narrating “ends” as complex historical transformations that involve survivals and continuities and thus blur before/after distinctions. Rather than providing a comprehensive and therefore existentially stabilizing overview of history, they draw attention to the indeterminate nature of ongoing processes of historical change. By focusing on the conceptual understanding of historical change that underwrites different kinds of end-time narratives, the essay clarifies the theoretical terminology of apocalypse and postapocalypse, and articulates a clearer understanding of the ways in which different kinds of contemporary stories about the end of the world are used to provide conceptual support for political action in the present.